Development of E-Learning Assisted Biology Learning Media on Excretion Material in Class XI at SMA Negeri 1 Maesaan - Paulus Exel Poli; Dientje F. Pendong; Metilistina Sasingga (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
This research aims to develop Biology learning media and determine the feasibility and response of students to E-Learning learning media at SMA Negeri 1 Maesaan, Maesaan District. Data was collected using interviews and questionnaires and then analyzed using quantitative methods with a descriptive analysis approach. Based on the research results on "Development of E-Learning Assisted Biology Learning Media on Excretory Material in Class XI at SMA Negeri 1 Maesaan". It was found that the results of the feasibility test carried out by media experts obtained a result of 93% or "very feasible" to be used with 3 aspects of assessment, namely, technology, content, and media operations. As well as the results of the feasibility test by material experts, the results obtained were 89% or "feasible" to be used with 3 aspects of assessment, namely the technology, content, and material aspects, and the test results of student responses to the E-Book learning media obtained results of 86% with 3 aspects of assessment, namely: 1. Motivation to learn 2. Media effectiveness, 3. Language and communication. The conclusions in this research show that the development stages use a 4D (four-D) model. This 4D (four-D) development model has 4 stages: Define, Design, Develop. Disseminate is very suitable for use by reviewing a feasibility test from media and material experts and looking at the test results of student responses to the excretion system material.